Biological Markers in Diagnosis of ADHD: Biologically Based Nosology for ADHD - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Oregon Health and Science University and other centers attempt to refine subtyping of childhood ADHD by using biologically based behavioral temperament types.